Form of Livelihood in Short Stories Anthology Pleasing Eyes by Ahmad Tohari - Grace, Gracia Agattha Marbun; Nurhayati Harahap; Sutan Lubis, Haris (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research aims to determine the form of livelihood in the short story anthology Mata yang Enak Dipandang by Ahmad Tohari. This short story anthology has a distinctive characteristic, namely that it expresses the lives of small or marginal communities in fulfilling their daily needs. This research uses literary anthropological analysis. The research method chosen was a qualitative approach. Data containing quotations containing livelihoods are used to realize various types of livelihoods or jobs. The results of the research found that there were 28 types of work as a form of livelihood, namely farmers, beggars, prostitutes, guard, security guards, RT heads, surau imams, kyai, cake sellers, food stalls, hawkers, rice traders, pecel traders, goods credit workers, massage therapists, toucan palak or thugs, pedicab drivers, fraudsters, novelists, shamans, waiters, pickpockets, police, pond entrepreneurs, stone workers, livestock breeders, regents and doctors. These jobs are done to make ends meet.